A.A. NAVIS DAN KARYANYA: STUDI HISTORIOGRAFI MENGENAI PERILAKU HIDUP BERAGAMA MASYARAKAT MINANGKABAU - Fithriah, Rahmuliani (Ensiklopedia of Journal, 2024)
The article examines the development of religious attitudes of the Minangkabau people with the object of research is the short stories of A.A. Navis which have been published under the title Complete Anthology of Short Stories of A.A. Navis, by Ismet Fanany published in 2005 by Kompas. The purpose of this study is to describe the development of religious life behavior of Minangkabau people as a representation of the social structure of Minangkabau society in 1955-2002. This research is a Historiographic research using content analysis method as a tool to interpret the text or manuscripts of A.A. Navis' short stories. The results of the research resulted in several conclusions, including the following: (1) Navis largely shows in the A.A. Navis Short Story Anthology that the religious attitudes of the Minangkabau (West Sumatra) community do not develop or change from time to time; (2) Some important things from Navis' short stories are as follows: (a) Regarding worship that does not have a balance between the world and the hereafter, (b) The association between men and women that exceeds the limits, and (c) Women's clothing that is no longer in accordance with religious values and Minangkabau customs, (d) The tradition of Eid in Minangkabau, even in Indonesia in general, has changed. What was originally intended to create a silaturrahmi relationship between fellow Muslims, has now turned into an unequal patron-client relationship, which widens the gap between the two.